Landslide classification, characterization and susceptibility modeling in KwaZulu-Natal - Singh, Rebekah Gereldene (My University, 2010)
In eastern South Africa landslides are widespread owing to the dramatic topographic-, climatic-, geological- and geomorphological-gradients across the region. In the KwaZulu-Natal (KZN) province numerous landslides and associated deposits are geohazards that represent threats to development and strategic infrastructure. The regional landslide inventory and susceptibility mapping project, following international classification systems and modeling techniques, has revealed the widespread occurrence of landslides. Landslide types mapped include; falls, topples, flows, translational and rotational slides. The bivariate statistical landslide susceptibility modeling method and Analytical Hierarchy Process (AHP) was used to evaluate landslide susceptibility, using a Geographic Information System (GIS). The huge size of some palaeo-landslides mapped is a revelation in the context of KwaZulu-Natal where recent landslide events are mainly small features triggered by intense rainfall events affecting embankments and steep hillslopes. Radiocarbon dating of organic material derived from sag ponds yielded minimum ages for the large middle to late Holocene landslide events.